Производные правила секвенциальных исчислений для конечнозначных логик с определителем равенства - Пынько, А.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The derivable rules of axiomatic extensions of sequent calculi with structural rules for the prepositional finitely valued logics with an equality determinant are analyzed with the use of methods of logic programming.